Anemia Berat pada Pembawa Sifat Thalasemia dengan Tuberkulosis Peritoneal: Sebuah Laporan Kasus - Fadilah, Tubagus Ferdi; Salsabila, Diva Azura; Farsyah, Muhammad Athar; Amelia, Ade (Fakultas Kedokteran Universitas Trisakti, 2025)
Thalassemia is a heterogeneous group of inherited hemoglobin disorders characterized by reduced or absent synthesis of globin chains, leading to varying degrees of ineffective erythropoiesis and chronic anemia. Thalassemia trait is usually regarded as a benign carrier state, often presenting with mild, asymptomatic microcytic anemia that does not require transfusion. In contrast, tuberculosis is a chronic infectious disease that commonly causes anemia of chronic disease through persistent inflammation, cytokine-mediated bone marrow suppression, and hepcidin-driven disturbances in iron metabolism. When these two conditions coexist, the resulting anemia may be more severe than expected from either condition alone.This report describes a unique case in which thalassemia is complicated by peritoneal tuberculosis, resulting in an unusually severe anemic state not typical for a carrier. A 15-year-old female receiving ongoing treatment for peritoneal tuberculosis presented with severe anemia (hemoglobin 7.43 g/dL). Physical examination revealed classic thalassemia signs, including facies cooley and splenomegaly. Laboratory findings confirmed severe microcytic, hypochromic anemia, and HPLC analysis showed elevated HbF and Hb Bart's, consistent with a thalassemia trait. The patient was managed with packed red cell (PRC) transfusions and folic acid, which successfully resolved the acute symptoms. As a conclusion, the severe anemia in this patient was likely due to multifactorial causes: an underlying thalassemia trait compounded by anemia of chronic disease (ACD) from tuberculosis. This case highlights the critical need to investigate comorbidities in thalassemia carriers with atypical presentations.